KESIAPAN ORGANISASI DALAM IMPLEMENTASI LEAN MANAGEMENT DI RSUD BAGAS WARAS KLATEN - Anggita Ratna Damayanti; Andreasta Meliala; Tjahjono Kuntjoro (Journal of Health Service Management, 2024)
RSUD Bagas Waras Klaten has some potential wastes of process which leads to the need of lean management to improve service quality and efficiency. Although implementation of lean management has been proven in improving quality, patient safety, effectivity, and cost efficiency, it is also potential to fail if some readiness elements are not met. Lean management readiness assessment is required to describe inhibiting as well as supporting elements in implementing lean management.